Acta Geodaetica et Geophysica - Acta Geodaetica et Geophysica (Springer Nature, 2026)
The journal publishes original research papers, methodology papers and reviews in the field of geodesy and geophysics under the following headings: aeronomy and space physics, electromagnetic studies, geodesy, geodynamics, geomathematics, geothermics, gravimetry, remote sensing, rock physics and mechanics, seismology, solid Earth physics, tectonics, history. Submissions dealing with problems of the Carpathian region and its broad surroundings are especially welcome, together with topics traditionally covered by Hungarian geodesists and geophysicists. The journal encourages the use of scientific colour maps, readable also by colour-vision deficient and colour-blind audience
FI 0.43
Q3
Keywords: Earth; Space & Environmental Sciences; Geology & Geophysics; Geología; Geofísica; Acuerdos transformativos; Transformative agreements; Geodesia; Geotermia; Física y mecánica de rocas; Sismología; Tectónica